2013
DOI: 10.1175/jhm-d-12-096.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Hydrological Simulations of Southeastern United States Watersheds to Temporal Aggregation of Rainfall

Abstract: This study investigates the sensitivity of the performance of hydrological models to certain temporal variations of precipitation over the southeastern United States (SEUS). Because of observational uncertainty in the estimates of rainfall variability at subdaily scales, the analysis is conducted with two independent rainfall datasets that resolve the diurnal variations. In addition, three hydrological models are used to account for model uncertainty. Results show that the temporal aggregation of subdaily rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…It is obvious from Figure that RMSE is significantly higher in 20CR‐RAS and 20CR‐KF in nearly all months, while the rest of the model simulations seem to display far more comparable RMSE. It should be however noted that observed diurnal variations over the SEUS in the winter and spring months are significantly lower than the rest of the year [ Bastola and Misra, ]. The monotonic decrease in RMSE from the summer months to December likely stems from the model's ability to simulate well the strong diurnal pattern of precipitation in the wet season.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious from Figure that RMSE is significantly higher in 20CR‐RAS and 20CR‐KF in nearly all months, while the rest of the model simulations seem to display far more comparable RMSE. It should be however noted that observed diurnal variations over the SEUS in the winter and spring months are significantly lower than the rest of the year [ Bastola and Misra, ]. The monotonic decrease in RMSE from the summer months to December likely stems from the model's ability to simulate well the strong diurnal pattern of precipitation in the wet season.…”
Section: Resultsmentioning
confidence: 99%
“…In the Southeastern United States (SEUS), diurnal variation of precipitation accounts for nearly 40% of the total seasonal variation in the summer [ Bastola and Misra, ]. In fact, the diurnal variation of rainfall is a considerably strong and persistent feature of SEUS climatology [ Dai et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…(Lin and Mitchell, 2005). From Bastola and Misra (2013). Seasonality in the temporal correlations between precipitation and surface temperature over Florida reveal that they change from positive correlations in the winter to negative correlations in the summer (Trenberth and Shea 2005;Misra and Dirmeyer 2009). In the winter time, surface evaporation that leads to cooling of the surface temperature is not an important contributor of moisture for local precipitation (Misra and Dirmeyer 2009).…”
Section: The Seasonal Cyclementioning
confidence: 99%
“…The high time frequency of radar data is also a determining factor (Michaud and Sorooshian, 1994;Bouilloud et al, 2010or Wetterhall et al, 2011. Results are sensitive to the radar time-step (Atencia et al, 2011;Anquetin et al, 2010;Bastola and Misra, 2013). O'Loughlin et al (2012) suggested that the calibration depends on the QPE time-step.…”
Section: Crucial Inputs For Ff Modelingmentioning
confidence: 99%